Comparison of diagnostic significance of the initial versus revised diagnostic algorithm for sarcopenia from the Asian Working Group for Sarcopenia. (July 2020) - Tabara, Yasuharu; Ikezoe, Tome; Setoh, Kazuya; Sugimoto, Ken; Kawaguchi, Takahisa; Kosugi, Shinji; Nakayama, Takeo; Ichihashi, Noriaki; Tsuboyama, Tadao; Matsuda, Fumihiko; ,
Highlights: Larger number of participants were identified as having sarcopenia by the revised AWGS algorithm for sarcopenia. The higher frequency of sarcopenia was attributed to changes in the cut-off values for slow gait speed and the addition of the 5-time chair-stand test as part of the assessment of physical performance. Physical characteristics of individuals diagnosed with sarcopenia by either algorithm did not differ markedly, but those with severe sarcopenia had significantly poorer physical performance even with a muscle mass similar to those with sarcopenia. The severity of sarcopenia was associated with carotid hypertrophy. Abstract: Backgrounds: Sarcopenia in older adults is a risk factor for age-related morbidity and mortality. This study aimed to clarify the diagnostic significance of the revised diagnostic algorithm for sarcopenia from Asian Working Group for Sarcopenia by comparing physical and clinical characteristics of individuals diagnosed with sarcopenia by the initial and revised algorithms. Methods: Study participants were 2061 older community residents. Skeletal muscle mass was measured by bioimpedance analysis. Handgrip strength and physical function required for the diagnosis of sarcopenia were measured by conventional methods. Carotid intima-media thickness was used as a marker of atherosclerosis in a large artery. Results: Using the initial algorithm, 60 of the participants were diagnosed with sarcopenia, but based on the revised algorithm, 89 had sarcopenia and 21 severe sarcopenia. The higher frequency of sarcopenia was attributed to changes in the cut-off values for slow gait speed and the addition of the 5-time chair-stand test as part of the assessment of physical performance. Physical characteristics of individuals diagnosed with sarcopenia by either algorithm did not differ markedly, but those with severe sarcopenia had significantly poorer physical performance even with a muscle mass similar to those with sarcopenia. There was a linear correlation between the severity of sarcopenia and carotid intima-media thickness (no sarcopenia: 0.94 ± 0.31, sarcopenia: 1.04 ± 0.41, and severe sarcopenia: 1.07 ± 0.55 mm, P = 0.003). Conclusion: The revised diagnostic algorithm was superior to the initial version at identifying individuals with sarcopenia and severe sarcopenia with a worse cardiovascular profile.